Metabolic improvements of novel microbial fermentation on black tea by Eurotium cristatum - Wang, Xiu-ping; Shan, Rui-yang; Li, Zhao-long; Kong, Xiang-rui; Hou, Ruo-ting; Wu, Hui-ni; Chen, Chang-song (Frontiers in Microbiology, 2023)
Due to its traditional fermentation, there are obvious limits on the quality improvements in black tea. However, microbial fermentation can provide an abundance of metabolites and improve the flavor of tea; in addition, there are many health benefits, such as lipid reduction, antimutagenic effects, and anti-tumor effects. The "golden flower" fungi are widely used in the microbial fermentation of tea and has unique uses in healthcare. To further explore the improvements in black tea quality achieved via microbial fermentation, we used widely targeted metabolomics and metagenomics analyses to investigate the changes in and effects of metabolites and other microorganisms during the interaction between the "golden flower" fungi and black tea. Five key flavor metabolites were detected, the levels of catechin, epigallocatechin gallate, (-)-epicatechin gallate were decreased by different degrees after the inoculation of the "golden flower" fungus, whereas the levels of caffeine and (+)gallocatechin increased. Botryosphaeriaceae, Botryosphaeriales, Dothideomycetes, Aspergillaceae, Trichocomaceae, and Lecanoromycetes play a positive role in the black tea fermentation process after inoculation with the "golden flower" fungi. D-Ribose can prevent hypoxia-induced apoptosis in cardiac cells, and it shows a strong correlation with Botryosphaeriaceae and Botryosphaeriales. The interaction between microorganisms and metabolites is manifested in tryptophan metabolism, starch and sucrose metabolism, and amino sugar and nucleotide sugar metabolism. In conclusion, the changes in metabolites observed during the fermentation of black tea by "golden flower" fungi are beneficial to human health, and this process relies on the assistance of Botryosphaeriaceae, Botryosphaeriales, Dothideomycetes, Aspergillaceae, Trichocomaceae, and Lecanoromycetes. This conclusion extends the knowledge of the interaction between the "golden flower" fungi and black tea, and it provides important information for improving the quality of black tea.